KETERKAITAN PRODUK WISATA TERHADAP KEPUTUSAN PENGUNJUNG BERWISATA DI DUSUN BAMBU LEISURE PARK BANDUNG - Nofiyanti, Fifi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2018)
This study aims to determine the tourism products contained in Dusun Bambu Bandung according to the tourist product. Because of the famous Bamboo Village among urban communities namely Jakarta, Bekasi, and Bogor. This research method is descriptive quantitative with quisioner measurement and survey location. using SPSS 22.00 program. The result shows that 43,7% of visitor decision is influenced by tourism product, while the rest of 56,3% influenced by other factor hence there is influence between tourism product to decision of visitor in Dusun Bambu Leisure Park with perfect significance 0.000. The result of t test hypothesis shows that tourism product gives a real influence to the decision of visitor in Bamboo Leisure Park hamlet that is equal to 16.391. Based on the results of the research, there are several suggestions for Dusun Bambu Leisure Park covering the addition of new attractions, maintaining the cleanliness of the surrounding environment, instilling good image to visitors, repairing damaged roads, balancing product prices and improving the quality of tourism products in order to increase the decision.